Effect of various natural feed on the growth and survival of Tinfoil barb larvae as local fisheries (Barbonymus schwanenfeldii) - Melanie Kavinta; Afriani Sari; Djamani Rianjuanda (BIO Web of Conferences)
Natural feed is needed to improve larvae growth, because of high nutritional value; appropriate size for the larvae's mouth opening; attracts the attention of fish and is easily digested by the larvae. The study purpose is to ascertain how various natural feed affect Tinfoil barb larvae's development and survival (Barbonymus schwanenfeldii). The study was carried out at the Lukup Badak Fish Seed Center, Pegasing, Central Aceh, from July to September 2022. A completely randomized design (CRD), comprising four treatments with four replications, namely: Treatment 1 (Artemia sp.), Treatment 2 (Rotifera sp.), Treatment 3 (Chlorella sp.), and Treatment 4 (Nannochloropsis sp.) was used for data analysis. Feeding was carried out ad libitum 4 times a day. The ANOVA result showed that feeding different natural feed to the Tinfoil barb larvae for 28 days significantly (P<0.05) effect on length rate and growth rate, but had no discernible impact on specific growth rate or survival (P>0.05). The highest length rate was found in the treatment of Artemia sp. (4.72 mm) while the highest weight rate was found in Rotifera sp. treatment (0.0119 g). Artemia sp. and Rotifera sp. are natural feed that have excellent nutrients for growth development of Tinfoil barb larvae.